Reductions using Clostridium sporogenes - Mordaka, Pawel Mateusz (2014)
Clostridium sporogenes was previously shown to be an extraordinary source for unusual reductases. It can catalyze reduction of wide a range of substrates such as nitroalkenes, enoates and nitro compounds, and can be used to generate chiral products.